2022
DOI: 10.3389/fcell.2022.840389
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mitochondrial Proteome Under Polyamines Treatment in Cardiac Aging

Abstract: Age-related alteration of mitochondria causes impaired cardiac function, along with cellular and molecular changes. Polyamines can extend the life span in mice. However, whether polyamines can affect the dynamic mitochondrial proteome, thereby preventing age-related changes in cardiac function and cardiac aging, remains unclear. In this study, we found that spermine (Spm) and spermidine (Spd) injection for 6 weeks could prevent 24-month-old rats heart dysfunction, improve mitochondrial function, and downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 128 publications
0
11
0
Order By: Relevance
“…Moreover, SPD can promote mitochondrial biogenesis and improve mitochondrial function in the aging heart ( 43 ). Polyamines spermine and spermidine can affect the dynamic mitochondrial proteome, thereby preventing age-related changes in cardiac functions and cardiac aging ( 36 ). Other studies have also demonstrated that SPD supplementary delay cardiac aging by enhancing mitophagy and promoting mitochondrial respiration in mice ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, SPD can promote mitochondrial biogenesis and improve mitochondrial function in the aging heart ( 43 ). Polyamines spermine and spermidine can affect the dynamic mitochondrial proteome, thereby preventing age-related changes in cardiac functions and cardiac aging ( 36 ). Other studies have also demonstrated that SPD supplementary delay cardiac aging by enhancing mitophagy and promoting mitochondrial respiration in mice ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing numbers of preclinical and clinical studies have indicated that dietary SPD has health effects such as antiaging, cardiovascular protection, neuromodulation, and anti-inflammatory functions, such as intraperitoneal injection of SPD (50 mg/kg) in mice protects against collagen-induced arthritis by inhibiting the polarization of M1 macrophages in synovial tissue ( 50 ). Supplementation with 10 mg/kg/d of SPD reversed age-related cardiac deterioration in rats ( 36 ). More importantly, the mother was an intervention with 5 mg/kg/d of SPD during late pregnancy to improve IUH-induced cognitive and neural function decline ( 51 ) and heart oxidative stress damage in rat offspring ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing to speculate that the increased transcriptional expression of Pdk4 in the aged heart in the baseline state may represent an adaptive response to the age‐induced mitochondrial dysfunction. Notably, recent attempts to downregulate Pdk4 to mitigate the effects of cardiac aging have been successful in baseline conditions signifying the link between Pdk4 and aging in normal physiology (Zhang et al, 2022 ). Under I/R stress, there is a larger abundance of pyruvate in the young mice than in the aged mice, consistent with transcriptional expression of Pdk4 being higher in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent attempts to downregulate Pdk4 to mitigate the effects of cardiac aging have been successful in baseline conditions signifying the link between Pdk4 and aging in normal physiology (Zhang et al, 2022). Under I/R stress, there is a larger abundance of pyruvate in the young mice than in the aged mice, consistent with transcriptional expression of Pdk4 being higher in young mice.…”
Section: Identification Of Novel Degs Provide Insight Towards Inadequ...mentioning
confidence: 99%